Eliciting information from small cells of sources. Issue 2 (2nd July 2016) - Granhag, Pär Anders; Oleszkiewicz, Simon; Kleinman, Steven
ABSTRACT: In past research, the Scharff technique has consistently outperformed different comparison techniques with respect to the elicitation of human intelligence. This study extends previous work by examining the efficacy of the Scharff technique applied to small cells of sources. The sources worked in triads ( N = 180), and were given information about a planned terrorist attack. They were then interviewed individually with either the Scharff technique (conceptualised as five tactics) or the Direct Approach (open and direct questions). The two techniques resulted in an equal amount of new information. As predicted, the sources in the Scharff condition underestimated, whereas the sources in the Direct Approach condition overestimated, their own contribution of new information. Furthermore, the Scharff tactics resulted in the sources overestimating the amount of information revealed by their fellow group members, whereas this was not the case in the Direct Approach. The paper advances the knowledge on elicitation techniques on several accounts: with respect to the context (focusing on small cells of sources), measures of efficacy (introducing a new dependent measure) and tactics (introducing novel context-dependent tactics). The outcome of the study marks the Scharff technique as a promising technique for eliciting information in intelligence settings.